Strategic Interactions of Bilateral Monopoly on a Private Highway - Judith Y.T. Wang; Hai Yang; Erik T. Verhoef (Tinbergen Institute, 2003)
This paper investigates strategic interactions between a private highway operator anda private transit operator who uses the same highway for its services. Heterogeneity oftravellers is taken into account by considering a continuous distribution of values of time.Demand elasticity arises from the inclusion of an outside virtual mode. Game theory is appliedto model the possible moves taken by the operators in their interactions. Four games areformulated, representing different decision making processes, including Nash and Stackelberg(leader-follower) games. The different timings of long-run and short-run decisions are alsomodeled in a two-stage game. Our results indicate that the market equilibria in the four gamesformulated are quite different as a result of the different sequences of moves. The highwayoperator is considered to be in a better position in terms of profit making in most cases,while for the transit operator it will generally be more advantag!eous to be the follower rather than in the leader position.
Keywords: R41; R48; D62; 330; Bilateral monopoly; private highway; private bus services; game theory; competitive equilibrium.; Autobahn; Straßenpersonenverkehr; Monopol; Spieltheorie